Lover come back [videorecording (DVD)] - Mann, Delbert, 1920-2007; Hudson, Rock, 1925-1985; Day, Doris, 1922-2019-; Randall, Tony; Adams, Edie, 1927-2008; Oakie, Jack, 1903-1978; Kruschen, Jack, 1922-2002 (Universal, 2004)
An adman and adwomen battle over a fake account and wind up in bed together.